STRATEGI GURU PAI DAN ORANG TUA DALAM MENANAMKAN PENDIDIKAN KARAKTER BAGI PESERTA DIDIK SMP NEGERI 14 RAJA AMPAT - Alqaf (Transformasi : Jurnal Kepemimpinan & Pendidikan Islam, 2025)
The purpose of this study is First to analyze how the strategies of Islamic Religious Education teachers in instilling character education in students of SMP Negeri 14 Raja Ampat. Second, to analyze how parental involvement helps Islamic Religious Education teachers in efforts to instill character education in students of SMP Negeri 14 Raja Ampat. This type of research is Qualitative Description. The research approach is the Islamic education approach and phenomenology. The research data sources are primary data sources and secondary data sources. The research data collection method uses observation, interview, and documentation methods. Data processing and analysis techniques use data reduction, data presentation, and conclusion.  The results of this study indicate that first, the strategy of Islamic Religious Education teachers in instilling character education in students of SMP Negeri 14 Raja Ampat is by strengthening through role models, strengthening through religious activities and extracurricular activities, strengthening integration with multicultural education, and collaboration strategies with parents and the community. Second, the participation of parents in helping Islamic Religious Education teachers in efforts to instill character education in students of SMP Negeri 14 Raja Ampat